2015
DOI: 10.1016/j.cardfail.2015.06.199
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Management and Outcomes of Heart Failure with Preserved Ejection Fraction in Patients Presenting to the Emergency Department with Acute Heart Failure

Abstract: Heart failure (HF) with preserved ejection fraction (HFpEF) represents 50% of the HF population. Although more common in women than men, there are limited data characterizing sex differences in the management and outcomes of HFpEF patients that present acutely to the emergency department (ED). Using data from the ADHERE-EM registry linked to Medicare claims, we conducted a retrospective analysis of patients presenting to the ED with acute HF. We identified patients with HFpEF (EF ≥40%) and stratified them by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 12 publications
3
7
0
Order By: Relevance
“…Although the data detail was not shown in the present study, prognostic impact regarding LVEF and gender would be an important issue and should be discussed. Females accounted for a higher proportion of the study population in some previous studies of HF patients with preserved EF values [12,26]. The results of the present study were consistent with this finding.…”
Section: Age Lvef and The Prognoses Of Female And Male Ahf Patientssupporting
confidence: 92%
See 2 more Smart Citations
“…Although the data detail was not shown in the present study, prognostic impact regarding LVEF and gender would be an important issue and should be discussed. Females accounted for a higher proportion of the study population in some previous studies of HF patients with preserved EF values [12,26]. The results of the present study were consistent with this finding.…”
Section: Age Lvef and The Prognoses Of Female And Male Ahf Patientssupporting
confidence: 92%
“…Although some previous reports have focused on patients with acute or advanced decompensated HF [7,8,11,13,25,26], all of the subjects in those studies were non-Japanese. Earlier studies suggest that female HF patients showed better survival [25]; however, some recent analyses have suggested that male and female patients show similar outcomes [7,8,11,13,26]. It has been reported that gender differences of HF patients may be affected by race [8].…”
Section: Female Worse Male Worsementioning
confidence: 99%
See 1 more Smart Citation
“…Similar to prior studies in patients with AHF, 2,3,9–14 women were older and had higher systolic blood pressure in this cohort. The baseline LUS findings were similar in women and men and consistent with the baseline CXR findings, with respect to the presence of vascular congestion, interstitial oedema, or alveolar oedema, and, likewise, findings on lung auscultation.…”
Section: Discussionsupporting
confidence: 85%
“…Prior studies report differing congestive patterns in women and men with AHF with regard to physical examination findings and symptoms at baseline. 2,3,9,10,12,14 In ADHERE and PROTECT, women with AHF demonstrated more pronounced pulmonary congestion at baseline with a higher prevalence of dyspnoea, 2 orthopnoea, 3 and rales, 2,3 although these differences were subtle in the ADHERE registry. By contrast, in the ALARM-HF registry and the RELAX-AHF trial, there were no significant sex differences in measures of pulmonary congestion based on dyspnoea, orthopnoea, or rales at baseline between women and men.…”
Section: Baseline Congestive Markers and Dynamic Changesmentioning
confidence: 99%